Analisis dan Perancangan Super CMS Pada PT Ruang Raya Indonesia - Sarip Hidayatuloh; Fatikah Aulia Farhah (Fakultas Teknik Universitas Persada Indonesia YAI, 2026)
PT. Ruang Raya Indonesia (Ruangguru) is an educational technology company focused on evelopingdigital learning platforms in Indonesia. One of the primary systems supporting its operations is SuperCMS, a content management systems designed to managed data and activities related to privatetutoring sessions between students and Masters teachers. Based on the findings of the observation, theexisting system still encounters several chalengges, including limited data integartion, the lack ofcomprehensive information displays, and workflows that are not yet fully efficient. To address theseissues, this study conducted the analysis and design of an information system using the waterfallmethodology. This approach consisted of data collection through observation and literature review,system requirements analysis, and systems modeling using the Unified Modeling Language (UML).The primary objective of this research is to design a Super CMS that can manage private tutoring sessions in a more informative, efficient, and integrated manner. The results indicate that the proposedSuper CMS design is capable of integrating scheduling, attedance tracking, assessment, andcommunication process into a single centralized platform. Furthermore, the develop user interfacefeatures a consistent design and intuitive navigation. The proposed system has the potential to improvethe effectiveness of data management, accelerate coordination among users, and provide o solidfoundation for future system implementation